Exploratory RNA-seq analysis in healthy subjects reveals vulnerability to viral infections during a 12- month period of isolation and confinement - Judith-Irina Buchheim; Jean-Noël Billaud; Matthias Feuerecker; Claudia Strewe; Carole Dangoisse; Andreas Osterman; Satish Mehta; Brian Crucian; Gustav Schelling; Alexander Choukér (Brain, Behavior, & Immunity - Health, 2020)
Exposure to stressful environments weakens immunity evidenced by a detectable reactivation of dormant viruses. The mechanism behind this observation remains unclear. We performed next generation sequencing from RNA extracted from blood samples of 8 male subjects collected before, during and after a 12-month stay at the Antarctic station Concordia. RNA-seq data analysis was done using QIAGEN Ingenuity Pathway Analysis (IPA) software. Data revealed the inactivation of key immune functions such as chemotaxis and leukocyte recruitment which persisted after return. Next to the activation of the stress response eIF2 pathway, interferon signaling was predicted inactivated due to a downregulation of 14 downstream genes involved in antiviral immunity. Among them, the interferon stimulated genes (ISGs) IFITM2 and 3 as well as IFIT3 exhibited the strongest fold changes and IFIT3 remained downregulated even after return. Impairment of antiviral immunity in winter-over crew can be explained by the downregulation of a battery of ISGs.